Innovations and Evolution of Metallurgy in Islamic Civilization of the Nusantara Region - Agus Pramono (Journal of Islamic History, 2025)
The study explores the transformation of metallurgy in Islamic civilization and its influence on the development of metalworking in Nusantara. Beginning with pioneers such as Khabab bin Al-Arat and Salman Al-Farisi, who introduced alloy technologies such as the creation of Zulfikar's sword, Islamic metallurgy advanced significantly with contributions from Jabir Ibn Hayyan and Reyhan Al-Biruni. This knowledge developed innovative methods, such as sublimation and nanostructure technologies, which found applications in weapons like the Damascus sword. The knowledge was later disseminated to Java by Sheikh Sadzali, who merged Islamic spiritual teachings with local traditions, particularly in keris-making, through figures like Mpu Supo Driyo and his son, Mpu Supo Mandraki. Collaborating with Sheikh Abdul Jalil, they integrated Islamic values into the symbolic designs of keris, blending functionality and spirituality. This research highlights the continuity of Islamic knowledge in advancing global technology while enriching local cultural heritage in Nusantara.  Keywords:    metallurgy,    islamic    civilization,    keris,   archipelago, damascus sword REFERENCES Pramono, A. (2018). The Existence of Metallurgical Science in Islamic Perspective. Journal of Character Education "JAWARA" (JPKJ), 4(1), 75-78. https://103.142.195.99/index.php/JAWARA/article/view/9529/0.  Pramono, A. (2022). Reyhan Al-Biruni's Fi Ma'rifat Al Jawahir: A Reference Book for the World's Metal Manufacturing Technology. Journal of Islamic History, 2(1), 12-23, UIN Salatiga, 7(1), 45-56. https://doi.org/10.53088/jih.v2i1.354.  Pramono, A. (2021). The book of the development of science & technology in an Islamic perspective (First print). Deepublish Publisher. https://www.deepublishstore.com/buku development-of-science/knowledge/. Pramono, A. (2022). The classical book of the Abbasid period as a reference for advanced military technology: A thought genealogy study. Millatī: Journal of Islamic Studies and Humanities, 7(1), 33-51. https://doi.org/10.18326/mlt.v7i1.7048. Sunyoto, A. (2012). Atlas of Walisongo: The first book to reveal the Wali Songo as historical facts (First Printing). Cooperation of IIMaN Library, Trans Pustaka, and LTN PBNU. Pages 123-130. Republika Khazanah. (August 4, 2011). The Story of the Prophet's Companions: Khabbab bin Arats, a Teacher in Knowledge and Sacrifice. Retrieved from https://khazanah.republika.co.id/berita/lpe4hn/kisah-sahabatnabi-khabbab-bin-arats-guru-dalam-ilmu-dan-pengorbanan.  Ibn Hisham. (1955). Sirah Nabawiyah. Beirut: Dar Al-Kutub AlIlmiyyah.  Tsuji, N., Saito, Y., Lee, S. H., & Minamino, Y. (1999). ARB (Accumulative Roll-Bonding) and other new techniques to produce bulk ultrafine-grained materials. Advanced Engineering Materials, 1(1), 15-23. https://doi.org/ DOI: 10.1016/S13596462(99)00015-9. Rahman, A. (2015). The Sword of Damascus: Medieval Islamic art and technology. Oxford: Islamic Publishing Press. Hoyland, R. G., & Gilmour, B. (2012). Medieval Islamic swords and sword-making. GetTextbooks.com. Paufler, P., Reibold, M., Levin, A. A., Kochmann, W., & Paufler, P. (2006). Carbon nanotubes in an ancient Damascus sabre. Nature, 444(7117), 286. https://doi.org/10.1038/444286a. Sunyoto, A. (2018). Atlas of Walisongo: Reconstructing the History of Walisongo. Jakarta: IIMaN Library. Reid, A. (1988). Southeast Asia in the Age of Commerce, 1450-1680: Volume One: The Lands Below the Winds. New Haven: Yale University Press. Poda Obunawa Manuscript Records: A Reference Source: Atlas of Walisongo,. 2012] Ricklefs, M. C. (2008). A History of Modern Indonesia Since c.1200 (4thed.). London: Palgrave Macmillan.